Розслідування ухилення від сплати податків: досвід ФРН та США - Біленчук, П.; Bilenchuk, P.; Філоненко, Г.; Filonenko, G. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проведено аналіз норм чинного податкового та кримінально-процесуального законодавства ФРН і США, якими регламентовано проведення податкових розслідувань у зазначених країнах. Акцентовано увагу на тому, що органи, які уповноважені проводити податкові розслідування у ФРН та США, використовують низку специфічних методів. Зроблено обґрунтований висновок, що використання інформаційно-аналітичних баз даних і сучасних засобів обміну інформацією можуть значно підвищити ефективність розслідування податкових злочинів.The article analyzes the regulations of the current tax law and criminal procedure legislation of Germany and the U.S., which regulate conducting tax investigations in those countries. Special attention is paid to the fact that the bodies responsible for conducting tax investigations in Germany and the U.S., use a number of specific methods. The high level of control over the movement of financial assets of taxpayers that has been achieved by extending the application of non-cash payments and using modern information databases and the creation of special investigative departments for investigation of tax crimes are effective tools of their detection and investigation. The reasonable conclusion is that the use of information and analytical databases and modern means of communication can greatly improve the effectiveness of the investigation of tax crimes.
The Investigation of Tax Evasion: the Experience of Germany and the U.S.A.
Keywords: ухилення від сплати податків; розслідування злочинів; зарубіжний досвід; tax evasion; crime investigations; foreign experience